Desentralisasi dan Demokratisasi di Desa: Membangun Akuntabilitas Publik Melalui Kultur Lokal - Pius Sugeng Prasetyo (Centre for Public Policy and Management Studies, 2005)
This work argues that developing democracy from the grassroots level is demanded in order to develop democracy in a broad scale. To issue and implement the new policies of decentralization after the fall of Suharto era should be noted as the radical change in managing the public affairs democratically. Even the local autonomy policies are implemented at the lowest level such as village area by introducing the modern democratic things i.e. the new political structure and the new political mechanism. One that should be emphasized that those political engineering is oriented to develop the public accountability as well. However, avoiding the local culture which is still exist in a such society will in fact raise problem, especially in the high pluralistic society like Indonesia. Local culture could be the fundamental element in developing democracy from the grassroots level.Kata kunci: desentralisasi, demokratisasi, kultur, akuntabilitas